Elucidating the Size‐dependent FRET Efficiency in Interfacially Engineered Quantum Dots Attached to PBSA Sunscreen. (10th February 2022) - Mubeen, Muhammad; Khalid, Muhammad Adnan; Mukhtar, Maria; Sumreen, Poshmal; Gul, Tehreem; ul Ain, Noor; Shahrum, Saba; Tabassum, Mamoona; Ul‐Hamid, Anwar; Iqbal, Azhar
Abstract: Applying sunscreen on human skin provides photoprotection against the harmful ultraviolet (UV) radiation of the sun. Sunscreen absorbs UV radiations and dissipates the absorbed energy through various radiative and nonradiative pathways. The attachment of functionalized quantum dots (QDs) to the sunscreen component is a novel idea to enhance the absorption cross‐section of UV radiations. Therefore, the attachment of the sunscreen component to the ligand functionalized biocompatible QDs and the absorbed energy transfer from sunscreen to the QDs could work as a model system to overall improve the efficiency of the sunscreen. This study elucidates the mechanism of size‐dependent Förster resonance energy transfer (FRET) efficiency and its rate between 2‐phenylbenzimidazole‐5‐sulfonic acid (PBSA) and mercaptoacetic acid (MAA) functionalized CdS QDs. In the PBSA‐QDs dyad, the PBSA (donor) dissipates UV‐absorbed energy to the CdS QDs (acceptor). Following excitation at 306 nm, the steady‐state photoluminescence (SSPL) and time‐resolved photoluminescence (TRPL) techniques measurements demonstrate that both the nonradiative energy transfer efficiency and rate are QDs size‐dependent in addition to donor‐acceptor distance, and suggest that bigger sized‐QDs result in an increase of the FRET efficiency. Abstract : This study demonstrates a unique and novel approach of the synthesis of mercaptoacetic acid (MAA) functionalized CdS quantum dots (QDs) and their attachment with 2‐phenylbenzimidazole‐5‐sulfonic acid (PBSA) sunscreen. In the PBSA‐QDs dyad, the PBSA (donor) transfers UV‐absorbed energy to the CdS QDs (acceptor). The Förster resonance energy transfer efficiency is greatly dependent on the size of the QDs that is controlled by concentration of the functionalizing ligand MAA in PBSA‐QDs dyads. The size of QDs exhibits an almost linear relationship with energy transfer efficiency and rate of energy transfer.